Strategi Promosi dalam Meningkatkan Volume Penjualan pada PT. Keraton Agri Nusantara - Soraya Nur Syifa (Universitas Islam Kadiri, 2023)
In marketing a product or service within a company, an easy and flexible approach (marketing mix) is needed. One of them is promotion, promotion is called the company's marketing communication mix including advertising, sales promotion, public relations, personal selling, and direct marketing. The purpose of this research is to formulate superior competitive marketing strategy alternatives and appropriate company policies using the SWOT (Strength, Weakness, Opportunity, Threat) analysis method at PT. Keraton Agri Nusantara. SWOT analysis is carried out using the IFE (Internal Factor Evaluation) matrix which describes the strengths and weaknesses of the company and the EFE (External Factor Evaluation) matrix which outlines the company's opportunities and threats and the IE (Internal External) matrix which shows the company's current position. From the results of data analysis obtained a total score of strengths, weaknesses, opportunities and threats, each obtained the highest strength weight 0.71, the highest weakness weight 1.10, the highest opportunity weight 1.25, and the highest threat weight 0.25. The average total score on the IFE matrix is 3.48 while the EFE matrix is 2.84. These results put PT. Keraton Agri Nusantara is in quadrant III and the marketing strategy that must be implemented is to minimize internal problems to seize existing opportunities.